The Influence of Social Media on the Marketing of Home-Based Bread MSME Products - Nanang Supriyadi; Gilang Ramadhan (International Journal of Economic and Tourism Research, 2025)
This study aims to analyze the impact of social media usage on the marketing effectiveness of homemade bread MSMEs in the digital era. Micro, Small, and Medium Enterprises (MSMEs), as the backbone of Indonesia's national economy, are currently facing significant challenges amid global competition and shifting consumer behavior. Marketing through social media platforms such as Instagram, Facebook, WhatsApp Business, and TikTok is considered an effective solution, offering low operational costs, broad market reach, and direct interaction with consumers. This research adopts a descriptive qualitative approach based on literature reviews and secondary data analysis to comprehensively understand this phenomenon. The analysis reveals that social media utilization has a positive influence on brand visibility, sales volume growth, and customer loyalty among homemade bread MSMEs. However, several challenges remain, including limited digital literacy, inconsistency in content creation, and underutilization of paid advertising features. These findings underscore the importance of strengthening the digital capacity of MSME actors through continuous training and multi-stakeholder collaboration to optimize social media-based marketing strategies. By leveraging social media effectively, homemade bread MSMEs have the potential to expand their market reach, enhance competitiveness, and reinforce business resilience in the face of an increasingly digitalized market landscape.